2020
DOI: 10.15446/rfnam.v73n2.82169
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the technology adoption in dairy agribusiness

Abstract: The adoption of adequate technologies is essential to improve the performance of different kinds of companies. Although there is literature related to the adoption of technology in dairy agribusiness in developed countries, information about it is scarce in developing countries. The objective of this study was to explore the factors associated with the adoption of technology by dairy agribusiness. A structural analysis was conducted to evaluate the relationships between the internal variables of Antioquia prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
1
8
0
3
Order By: Relevance
“…Similar results have been described in other developing countries, since several authors who have worked with small-scale agricultural producers indicate that most of the production units have a low technological level or that the most technified SSDPU represent between 12% and 33% of the total analysed [ 19 , 42 , 43 , 44 , 45 ]. These authors focus their research on analysing the technological level of each identified cluster, but they do not put emphasis on describing the factors that determine the survival and prevalence of SSDPU with a low technological level, which highlights the importance of this study.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similar results have been described in other developing countries, since several authors who have worked with small-scale agricultural producers indicate that most of the production units have a low technological level or that the most technified SSDPU represent between 12% and 33% of the total analysed [ 19 , 42 , 43 , 44 , 45 ]. These authors focus their research on analysing the technological level of each identified cluster, but they do not put emphasis on describing the factors that determine the survival and prevalence of SSDPU with a low technological level, which highlights the importance of this study.…”
Section: Discussionsupporting
confidence: 82%
“…Some studies focused on the characterisation of animal production systems argue that, as SSDPU adopt a higher technological level, they have more possibilities of being competitive and thereby sustainable [15,22,42], and the higher the productivity of the SSDPU, the better they are able to face the costs and conditions imposed by the market [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) (2) siendo ANO t el activo neto operacional del período. La variable es la suma del capital de trabajo neto operativo KTNO t y del activo fijo neto operacional AFNO t : El KTNO t es la diferencia entre el activo circulante y el pasivo corriente que no tienen costo explícito.…”
Section: Marco Teóricounclassified
“…Telah banyak penelitian terkait upaya pengembangan komoditas susu yaitu upaya peningkatan produksi susu berdasarkan rantai produksi susu di Brazil [16], beberapa faktor yang memberi pengaruh terhadap penerapan teknologi dalam agribisnis susu [3], dampak sosial dan ekonomi pada peternakan sapi perah skala kecil di Tanzania [15], dan perbandingan kondisi sistem produksi susu di Brazil dan Belanda [17]. Akan tetapi, publikasi ilmiah yang berkaitan dengan pengembangan agribisnis komoditas susu sapi perah Kabupaten Tulungagung masih minim untuk dijumpai.…”
unclassified